ANALISIS KESALAHAN BERBAHASA PADA SOAL UJIAN PELAJARAN BAHASA INDONESIA DI SMA - Shinta Wardani; Budhi Setiawan; Sri Hastuti (Universitas Sebelas Maret, 2020)
This research aims to describe and explain: (1) the kinds of mistakes-speaking on the matter, (2) the cause of the error on the question of language, (3) communication effects caused due to an error on a question of language Final Assessment subjects Indonesian Language grade XI public senior high school in Sukoharjo Area school, (4) understanding teacher against the rule drafting problem , and (5) precision drafting problem Final Assessment subjects Indonesian Language grade XI public senior high school in Sukoharjo based on rules of preparation of a matter. This type of research is qualitative research. Qualitative research this time is both a content analysis (content analysis) with the main data source about the Final Assessment of the Odd Semester subjects Indonesian Language grade XI public senior high school in Sukoharjo . The technique of sampling with purposive sampling and snowball sampling. This research uses data sources triangulation and triangulation method as a test of the validity of the data. The results of the analysis of the findings can be explained as follows. First, errors in language reserved assessment of the end of the Semester in the form of spelling errors, Word, and sentence. Second, language mistakes caused by internal factors and external factors. Internal factors in the form of less understand linguistic rules, the lack of rigour in drawing up the question, a habit of relying on a team of editing, and the wrong habits. While external factors in the form of the mistakes of other languages, is vulnerable for a short time, and there is no evaluation. Third, the effect of communication language errors are significant because the learners feel difficulty in understanding the intent of the question. Fourth, teachers less understand rule drafting reserved either in theory or practice. Fifth, the question of the drafting of the Rules contained in the matter of the assessment of the finalsemester subjects Indonesian Language grade XI public senior high school in Sukoharjo is not fully using the rules of preparation of the matter that is being applies both from the aspect of material and construction aspects.